Drivers and mechanisms of cropland abandonment in typical mountainous areas of Southwestern China - Yu, Hao; Zhao, Zhongqiu; Yang, Qiao (Frontiers in Sustainable Food Systems, 2025)
Cropland abandonment has become a common phenomenon globally, which not only causes waste of land resources, but also affects agricultural development and food security. As the largest developing country, China has witnessed particularly severe cropland abandonment under the combined effects of socioeconomic transformations and policy adjustments, especially in its southwestern mountainous regions. To systematically investigate the status and determinants of cropland abandonment in typical mountainous areas of China, this study employed multilevel regression analysis based on household surveys to construct a three-level “plot-household-village” Logit model. The research systematically examined influencing factors and driving mechanisms of cropland abandonment, providing scientific evidence for regional land management. The results reveal an abandonment rate of approximately 10.4% in typical mountainous areas of Southwestern China. Spatially, the abandonment rate demonstrates an inverse correlation with elevation, a parabolic relationship with cultivation distance (initially increasing then decreasing), and positive correlations with declining land quality and increasing slope gradient. Regarding determinants, plot-level land quality emerged as the most critical explanatory factor (coefficient = 0.623). At household level, degree of part-time farming and agricultural labor density per unit area showed significant impacts (coefficients = 0.350 and −1.011 respectively). Village-level analysis identified per capita cultivated land area as the primary determinant, exhibiting a significant negative correlation (coefficient = −1.166). These multi-scale factors interact synergistically, forming a complex hierarchical driving mechanism for cropland abandonment. The findings highlight the necessity for differentiated land management strategies that account for scale-specific characteristics in mountainous regions.